High-performance and compact integrated photonics platform based on silicon rich nitride–lithium niobate on insulator - Xingrui Huang (AIP Publishing LLC, 2021)
In this paper, a silicon rich nitride–lithium niobate on insulator hybrid platform with waveguides and several key components is proposed. The propagation loss of the silicon rich nitride–lithium niobate rib-loaded waveguide (300 × 300 nm2) is 0.86 dB/cm at 1550 nm. Passive devices, including adiabatic power splitters, multimode interferometer-based splitters, asymmetrical Mach–Zehnder interferometers, and Bragg grating filters, are fully designed and characterized. Moreover, we report a Mach–Zehnder modulator with high-speed modulation up to 120 GBaud without digital compensation. The electro-optical response with 1 dB roll-off at 40 GHz is obtained, and the 3-dB modulation bandwidth is predicted to be >100 GHz. Hence, the proposed platform enables high-performance passive and active devices with low loss and high integration density, making it a promising candidate for emerging photonics integrated circuits.